Enzymatic and antagonistic potential of bacteria isolated from typical fruit of Cerrado in Minas Gerais State, Brazil (Acta Scientiarum. Agronomy, 2015)
Brazil has great biodiversity, which is observed in the Cerrado biome of the tropical Brazilian savanna. The objectives of this study were to isolate and identify bacteria from Psychotria hoffmannseggiana with potential cellulase and pectinase production and with antagonistic activity against Aspergillus carbonarius, an Ochratoxin A (OTA) producer. Ripe fruit were collected in the region of Passos City in the preserved Cerrado area in Minas Gerais State, Brazil. Serial dilutions were performed, and the bacteria isolated were biochemically characterized and identified by sequencing. To analyze the production of enzymes, the bacteria were cultivated in CMC and pectinase media. The better enzyme producers were optimized for production. Assays on the antagonistic activity for growth and sporulation were carried out in co-culture (bacteria and filamentous fungi). TLC was performed to verify the mycotoxin production. The predominant microbiota were Gram-negative bacteria belonging to the Enterobacteriaceae family. Some isolates showed potential for enzymatic and antagonistic activity, especially the isolate identified as Lysinibacillus fusiformis. This species was a better producer of cellulases (maximum activity: 103.1 mg glucose min.-1 mg-1 protein). In conclusion, the bacteria isolated from Psychotria hoffmannseggiana showed biotechnological potential for agro-industry and the environmental aspect.